1989
DOI: 10.1530/acta.0.1200724
|View full text |Cite
|
Sign up to set email alerts
|

The effect of long-term pulsatile GnRH administration on the 24-hour integrated concentration of GH in hypogonadotropic hypogonadic patients

Abstract: Measurement of integrated concentration of GH by means of continuous withdrawal sampling is a method of evaluating physiological hormonal secretion. Integrated concentration of GH was evaluated in 5 subjects with idiopathic hypogonadal hypogonadism (range 19\p=n-\27 years) and in a 17-year-old male with idiopathic delay of puberty (5 males, 1 female) before and 30\p=n-\240 days after the start of pulsatile GnRH administration. Gonadotropins and testosterone or 17\g=b\-estradiol were restored, whereas 24-h inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In addition, we found a decline directly after menarche, which has not previously been reported. The increase is mainly the result of an increased GH pulse amplitude as it is in boys (11,(21)(22)(23). Mean GH level and the fraction of GH in pulses increase 2-3 fold during this pubertal period.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, we found a decline directly after menarche, which has not previously been reported. The increase is mainly the result of an increased GH pulse amplitude as it is in boys (11,(21)(22)(23). Mean GH level and the fraction of GH in pulses increase 2-3 fold during this pubertal period.…”
Section: Discussionmentioning
confidence: 91%
“…Estrogens have been implicated to increase spontaneous secretion of GH as well as secretion in response to provoca¬ tive stimuli (6)(7)(8)(9). Furthermore, during GnRH-in¬ duced puberty, a concurrent increase in GH secre¬ tion was reported in hypogonadotropic female patients (10,11). Therefore, stimulation of the go¬ nadal axis seems to result in an increased GH se¬ cretion.…”
mentioning
confidence: 99%
“…Several studies have shown that in men, regardless of age, testosterone centrally increases the GH level, followed by IGF-I production through the push effect. 36 40 Studies were performed to determine whether testosterone enhances IGF-I directly or as a costimulatory factor to GH; testosterone alone had a very limited or no effect on circulating IGF-I levels except in the presence of GH. 41 43 On the contrary, there is a debate concerning the relationship between estrogen and GH/IGF-I.…”
Section: Factors Affecting Plasma Levels Of Gh/igf-imentioning
confidence: 99%
“…In adults, the relationships between gonadal and GH status are strong for men but appear less so for women. GH secretion is reduced in men with hypogonadism regardless of cause and is normalized by androgen replacement or by pulsatile GnRH treatment in those with hypogonadotrophic hypogonadism 17–20 . In women the relationship between oestrogen and GH levels is inconsistent.…”
Section: Neurosecretory Modulationmentioning
confidence: 99%
“…In pre‐ and peripubertal boys, testosterone in physiological and pharmacological doses increases spontaneous and stimulated GH secretion 12,24,25 . In hypogonadal and elderly men, testosterone and GnRH treatment, respectively, increase spontaneous and stimulated GH secretion 17–20,26,27 . The stimulatory action of testosterone on the GH axis appears to be mediated at the hypothalamic level by GHRH 19 .…”
Section: Neurosecretory Modulationmentioning
confidence: 99%